Pengaruh Pengembangan Karir Terhadap Prestasi Kerja Guru SMP Negeri 47 Palembang - Daffa Akbar Redian; Agustina Hanafi; Parama Santati; Isni Andriana (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
This research aims to determine the effect of career development on teacher work achievement at SMP Negeri 47 Palembang. The population in this study were all teachers at SMP Negeri 47 Palembang using a sample of 41 respondents. The data collection method used in the study was obtained from a questionnaire. The analysis technique used is simple linear regression analysis. The data obtained were tested using validity test, reliability test, simple linear regression test, analysis of correlation coefficient (r) and coefficient of determination (R2), as well as hypothesis testing or t test. The test was carried out using the statistical package for social science (SPSS) version 21. Based on the results of the analysis, it was concluded that career development had a positive and significant effect on teacher work achievement at SMP Negeri 47 Palembang. Keywords: Teacher, Work Achievement, Questionnaire, Career Development.